Cancer-Associated Venous Thromboembolism—Diagnostic and Therapeutic Considerations: An Update Based on the Revised AWMF S2k Guideline - Riess, Hanno; Beyer-Westendorf, Jan; Pelzer, Uwe; Klamroth, Robert; Linnemann, Birgit (Hämostaseologie, 2023)
Patients with cancer are prone to develop venous thromboembolism (VTE) with negative impact on quality of life, morbidity, and mortality. Treatment of established VTE is often complex in patients with cancer. Treatment of cancer-associated VTE (CAT) basically comprises initial and maintenance treatment, for 3 to 6 months, secondary preventions, and treatment in special situations. Therapeutic anticoagulation is the treatment of choice in CAT. In addition to the efficacy and safety of low-molecular-weight heparin (LMWH) that had been recommended for decades, direct oral anti-factor Xa inhibitors, a subgroup of direct oral anticoagulants (DOACs), demonstrated their advantages along with the accompanying concerns in several randomized controlled treatment trials of CAT. The latest guidelines, such as the German AWMF-S2k Guideline “Diagnostics and Therapy of Venous Thrombosis and Pulmonary Embolism,” agree with each other on most aspects with respect to the treatment of CAT. Encompassing recent clinical studies, and meta-analyses, as well as the focus on some special management aspects of CAT, the objective of this review is to present a current overview and recommendations for the treatment of CAT.
Keywords: venous thromboembolism; cancer; anticoagulation